2019
DOI: 10.3390/su11216057
|View full text |Cite
|
Sign up to set email alerts
|

Product Segmentation and Sustainability in Customized Assembly with Respect to the Basic Elements of Industry 4.0

Abstract: Sustainable manufacturing is not just about manufacturing, but also products and services. In the area of custom production processes, there may also be circumstances of organizational management where compliance with labor productivity and the due-date principle is problematic. Similar products with different operating times cause the throughput of assembly lines to slow down, increase number of works in progress (WIP), and increase productivity waste. It is possible to reduce this impact through various prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…In the context of Tunisia, there are very few studies found using the concept of MI approach for measuring productivity changes across various sectors. Two studies were identified focusing on the evaluation of productivity changes across the Tunisian schools and educational institutions [39][40][41][42][43]. Zrelli and Belloumi [44] used MI for investigating the impact of environmental strategies on the Tunisian manufacturing industry during 1994-2008 by using data from 26 industries and found an average increase of 1.5% a year.…”
Section: Background Studymentioning
confidence: 99%
“…In the context of Tunisia, there are very few studies found using the concept of MI approach for measuring productivity changes across various sectors. Two studies were identified focusing on the evaluation of productivity changes across the Tunisian schools and educational institutions [39][40][41][42][43]. Zrelli and Belloumi [44] used MI for investigating the impact of environmental strategies on the Tunisian manufacturing industry during 1994-2008 by using data from 26 industries and found an average increase of 1.5% a year.…”
Section: Background Studymentioning
confidence: 99%
“…One of the main trends nowadays is a shift away from mass series production and a transition to custom production based on the increasing requirements of demanding customers [ 8 , 32 ]. The consequence of this trend is often several variations of the same product on one production line at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the economic impact is the most influential factor in I4.0 developments. The reduction in operating costs and the improvement of manufacturing speed and production as well as process quality through end-to-end digital integration is one of the major drivers for I4.0 investments [93,124,125]. However, these investments must be weighed against the high costs of implementation [64].…”
Section: Review Discussion and Findingsmentioning
confidence: 99%